Epic tails [videorecording (DVD)] - Alaux, David; Tosti, Eric; Tosti, Jean-François (Viva Pictures, 2025)
Pattie, an ambitious and daring mouse has big dreams to be an adventurer and a hero. When her homeland in Ancient Greece is threatened by Poseidon himself, Pattie is determined to save her city.